PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING PADA PELANGGAN RAMAYANA DEPARTMENT STORE MALL DINOYO CITY MALANG - Novandy Novandy; N. Rachma; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTTarget of this research is to know and analyse influence quality of serviceto loyalty. To know and analyse influence quality of service to satisfaction. Toknow and analyse influence satisfaction to loyalty. To know and analyse influencequality of service to loyalty through satisfaction as variable of intervening.This study type is survey. This research done in customer RamayanaDepartment Store Mall Dinoyo City Malang. Population in this research is allcustomer which have bought in Ramayana Department Store Mall DinoyoMalang in February 2017 counted 1348 customer. research sampel amount to 93responder with sampling technique purposive sampling.Result of research show there are direct influence is quality service toloyalty customer Ramayana Department Store Mall Dinoyo Malang. There aredirect influence is quality of service to satisfaction of customer RamayanaDepartment Store Mall Dinoyo Malang. There are direct influence satisfaction toloyalty customer Ramayana Department Store Mall Dinoyo Malang. Quality ofservice have an effect to loyalitas through satisfaction as variable of intervening.Keywords: Quality Service, Loyaly, Satisfaction